Dynamics and politics of policy change - Chowdhury, Tawfiq-e-Elahi; Haggblade, Steven (International Food Policy Research Institute, 2000)
For drama and intrigue, the story of food policy reform in Bangladesh is difficult to match. Played out over two decades, since the 1970s, this fascinating and complex tale has involved powerful interest groups, including at least three different governments of Bangladesh, half a dozen key food-aid donors, millions of ration recipients, 10,000 ration shop dealers, an equal number of officials managing government food programs, and more than 1,700 millers who supply government rice (Table 9.1). Motives and tactics have changed over time, with the principals exhibiting a wide range of behavior—from idealism to opportunism; from gentle persuasion, to explicit conditionality, to the application of military force—and, not least, patience and guile.